MENINGKATKAN AKURASI GRAMATIKAL PROPOSAL PENELITIAN BERBAHASA INGGRIS MAHASISWA STAIN JURAI SIWO METRO MELALUI TEKNIK PEER-CORRECTION - Arini, Yusti (JURNAL TAPIS, 2011)
Grammar is one of the important aspects in writing; therefore, when learning writing, the students must produce a text that is grammatically accurate. On the other hand, the lecturer must apply an appropriate technique to increase the studentsâ writing ability. Peer-correction is considered to be appropriate technique because of its strengths. This Classroom Action Research is aimed at knowing whether this technique can increase the studentsâ writing ability; especially in grammar aspect. The subject consisted of 40 English study program students of State Islamic College of Jurai Siwo Metro. The results show that, in Cycle 1, there is an increase of the posttest score (77.24) compared with that of pretest (77.24). Also, In Cycle 2, the posttest score (78.41) is higher than that of the first posttest. Meanwhile, the posttest score of Cycle 3 is 74.05, lower than that of the second posttest. However, it can be concluded that the Peer-correction technique can increase the grammatical accuracy of the studentsâ research proposal.Â Keywords: grammatical accuracy, research proposal, peer-correction technique, cycle, pretest, posttest, increase